Rola Internetu w procesie konsumpcji gospodarstw domowych - Wałęga, Grzegorz (The Role of the Internet in Household Consumption Patterns, 2009)
One of the most remarkable developments over the past years has probably been the way in which the Internet has infiltrated, and become an important part of household consumption patterns. The objective of this paper is to present main changes of household consumption patterns, which are caused by technical progress. The author discusses changes in level of expenditure on communication and its share of the total household expenditure in Poland in the period of 1994-2007. The paper also identifies households which regularly use computers or the Internet. Special attention is given to the activities carried out on the Internet for private purposes. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 431-443